PENGARUH OPERATING LEVERAGE DAN FINANCIAL LEVERAGE PADA EPS MELALUI NET INCOME - Harlyn Lindon Siagian; Samuel Steve; Sarah Marchia Tabita (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2020)
The objects of the research to determine whether operating leverage and financial leverage affect earnings per share with net income as a moderator. Descrptive methods was used in this research. Quantitative data was used in the form of financial statements from the website of Indonesia Stock Exchange in 2014-2018. The population in this research was companies listed on the Indonesia Stock Exchange (IDX). The sample of this research were the oil and gas subsector companies, and the metal and mineral subsector listed on the Indonesia Stock Exchange (BEI) in 2014-2018 as many as 17 companies with 85 samples. Partially financial leverage has an effect on earnings per share. Operating leverage through net income has no significant effect on earnings per share and financial leverage has a significant effect on earnings per share with net income as an intermediary.